(untitled) (Research, Society and Development, 2023)
Objective: To understand the importance of the nursing professional’s contribution in identifying and monitoring women who are victims of sexual violence. Methodology: integrative literature review. The guiding question was: aiming to address the problem of how the nursing professional contributes to the identification and monitoring of women victims of sexual violence. The descriptors were: woman and; sexual violence and; nursing care. Searches were carried out in the BDENF databases, SciELO electronic library and GOOGLE ACADÊMICO, which integrates the aforementioned databases. After applying the inclusion and exclusion criteria, 20 articles were selected for the final sample. Based on the results, nursing care for women who are victims of sexual violence. These showed that there are gaps in relation to the care provided by nursing professionals, whether in the form of reception/approach/care, as well as the non-use of specific care protocols, with failures in the referral of cases. Furthermore, it was observed that where a humanized reception took place, women felt more comfortable reporting what had happened. Conclusion: It is imperative that health professionals, especially nurses, are aware of this complex care, train themselves in the effectiveness of actions, provide comprehensive care and allow women who have as little physical contact as possible to understand the complexities of physical pain which can have a strong emotional impact and disrupt their lives and ways of living.